In vitro and in silico hormonal activity studies of di‐(2‐ethylhexyl)terephthalate, a di‐(2‐ethylhexyl)phthalate substitute used in medical devices, and its metabolites. Issue 7 (8th March 2019) - Kambia, Nicolas K.; Séverin, Isabelle; Farce, Amaury; Moreau, Emmanuel; Dahbi, Laurence; Duval, Claire; Dine, Thierry; Sautou, Valérie; Chagnon, Marie‐Christine
Abstract: Plasticizers added to polyvinylchloride used in medical devices can be released into patients' biological fluids. The substitution of di‐(2‐ethylhexyl)phthalate (DEHP) by alternative plasticizers is essential but their safety must be demonstrated. DEHP, di‐(2‐ethylhexyl)terephthalate (DEHT) and their metabolites were investigated using level 2 Organization for Economic Co‐operation and Development bioassays to screen for in vitro hormonal changes. Differences between the DEHP and DEHT metabolites were observed. Albeit weak, the hormonal activities of DEHT‐derived metabolites, e.g., 5‐OH metabolite of mono‐(ethylhexyl)terephthalate (5‐OH‐MEHT), were detected and the results of docking experiments performed on estrogen receptor alpha and androgen receptor agreed with the biological results. A co‐stimulation of human estrogen receptor alpha and human androgen receptor was also observed. With regard to steroidogenesis, a 16‐fold increase in estrogen synthesis was measured with 5‐OH‐MEHT. Therefore, even if DEHT remains an interesting alternative to DEHP because of its low migration from medical devices, it seems important to verify that multi‐exposed patients in neonatal intensive care units do not have urinary levels of oxidized metabolites, in particular 5‐OH‐MEHT, suggesting a potential endocrine‐disrupting effect. Abstract : Plasticizers as di‐(2‐ethylhexyl)terephthalate (DEHT) are added to PVC used in medical devices can be released into patients' biological fluids. The objective of this study was to investigate the potential endocrine‐disrupting effects of DEHT and its metabolites in silico and in vitro. The hormonal activities of DEHT‐derived metabolites, e.g., 5‐OH metabolite of mono‐(ethylhexyl)terephthalate (5‐OH‐MEHT), were detected and the results of docking experiments performed on estrogen receptor alpha and androgen receptor agreed with the biological results. A co‐stimulation of human estrogen receptor alpha and human androgen receptor and an increase in estrogen synthesis was measured with 5‐OH‐MEHT.